Diagnóstico e diretrizes para a gestão de aspectos sociais e ambientais no APL de móveis de João Pessoa-PB - Riul, Marília (2010)
Productive and management strategies that emphasize social and environmental aspects are crucial in the context of social and environmental crisis. The furniture industry is an activity that needs attention, in face of the various environmental aspects and impacts involved in its activity, like the exaggerated volume of waste of production, the overexploitation and waste of wood and the use of toxic substances. Furthermore, the furniture production is predominantly performed by micro and small enterprises (MSEs), what results in incipient strategies of environmental management. This research intended to present a diagnostic of the behavior of the furniture enterprises that participates of the local production system (LPS) of the furniture sector in João Pessoa, Paraíba, in relation to social and environmental aspects. The chosen methods for the data collection were interviews to the businesses owners and direct observations in the enterprises. The results diagnosed that the studied enterprises still do not behave proactively in relation to various social and environmental aspects of the activity, and sometimes disclaim any responsibility on the grounds that the MSEs did not exert negative pressure on the environment and society. We highlight the problem of inadequate waste management, which triggers series of social and environmental risks such as pollution and damage to workers' health. From the diagnosis, it was possible to systematize recommendations for improving the environmental performance of companies in the LPS, based on the principles of unity and cooperation among enterprises.